Aura - Fuentes, Carlos ([New York : Farrar, Straus and Giroux], 1975)
A young scholar falls passionately in love with the niece of an aged widow and discovers the true relationship between the two women.
Translation of: Aura.
English and Spanish.
Keywords: Spanish fiction; Mexican fiction; Bilingual books -- Fiction; Bilingual books -- Spanish -- Fiction; Spanish fiction -- Translations into English; Mexican fiction -- Translations into English; Science fiction, Spanish -- Translations into English; Science fiction, Spanish; Love stories; Horror tales